When Curating Faces History. (2nd October 2018) - Jacob, Mary Jane
Abstract: The exhibition at Marlborough Galleries, New York, took place in 2015 and on the occasion of the Magdalena Abakanowicz's 85th birthday. This article celebrates her creative production, a personal expression as well as her faith in the endurance of culture. It represents a survey of sorts, beginning with her 1978 Abakan Last . In the 1970s and 1980s, the body in burlap, at once particular yet unidentified, began to populate her oeuvre. Crowd III (1989) and Figure in Iron House (1989–1990) are testaments to the power and poignancy that she fashioned from a humble medium: woven fiber. It also references one of her great outdoor works produced for the city of Chicago in 2006. It is located in Grant Park along the south terminus of a lakefront stretch at Roosevelt and Michigan Avenue. It is Abakanowicz's largest outdoor work, Agora, 106 9-feet tall, cast-iron walking figures.